2020
DOI: 10.1002/adem.202001116
|View full text |Cite
|
Sign up to set email alerts
|

Fast and High‐Throughput Synthesis of Medium‐ and High‐Entropy Alloys Using Radio Frequency Inductively Coupled Plasma

Abstract: Multiprincipal element alloys, or medium-and high-entropy alloys (MEAs and HEAs), hold great potential for numerous structural and functional applications, yet the synthesis of such alloys out of a vast composition space is a daunting task. Herein, a radio frequency inductively coupled plasma (RF-ICP) method for preparing bulk MEAs and HEAs in a rapid and high-throughput fashion is reported. Typical MEAs and HEAs are successfully synthesized within 40 s per alloy, thereby greatly improving the fabrication effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…It is beneficial to use a neural network to determine process windows in a fast and effective way. Similar high-throughput approaches have been employed for selective laser melting and fabrication of high-entropy alloys (HEAs) Cold-sprayed materials exhibit heterogeneous microstructure, resulting in non-uniform mechanical property distributions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is beneficial to use a neural network to determine process windows in a fast and effective way. Similar high-throughput approaches have been employed for selective laser melting and fabrication of high-entropy alloys (HEAs) Cold-sprayed materials exhibit heterogeneous microstructure, resulting in non-uniform mechanical property distributions.…”
Section: Discussionmentioning
confidence: 99%
“…It is beneficial to use a neural network to determine process windows in a fast and effective way. Similar high-throughput approaches have been employed for selective laser melting and fabrication of high-entropy alloys (HEAs) …”
Section: Discussionmentioning
confidence: 99%
“…4(e). 60) Typical samples were fabricated within 40 s per alloy, thereby significantly improving the fabrication efficiency and throughput. More specific reviews on DFT and screening are available elsewhere.…”
Section: Screening Via High-throughput Experimentsmentioning
confidence: 99%
“…[22] The improved properties, especially superior mechanical performances brought by the microstructure of MEA have been widely reported in recent years. [23][24][25][26] A study on a Fe-based MEA catalyst reported outstanding activity and stability, [27] where the MEA thin film overperformed its HEA counterpart with lower oxygen evolution reaction (OER) overpotential values. [28,29] Noble metal-based MEA thin films are further expected to have better performance in electrocatalysis; however, the facile synthesis of MEA films remains challenging.…”
Section: Introductionmentioning
confidence: 99%